IFI6 Inhibits Apoptosis via Mitochondrial-Dependent Pathway in Dengue Virus 2 Infected Vascular Endothelial Cells - Qi, Yiming; Li, Ying; Zhang, Yingke; Zhang, Lin; Wang, Zilian; Zhang, Xuzhi; Gui, Lian; Huang, Junqi (PloS one, 2015)
Dengue hemorrhagic fever (DHF)/Dengue shock syndrome (DSS) is a fatal infectious disease that demands an effective treatment. Interferon (IFN)-stimulated genes (ISGs) induced by dengue virus (DENV) exert antiviral effects. Among ISGs, IFN-α inducible gene 6 (IFI6) was increased in DENV infected human umbilical vascular endothelial cells (HUVECs) by microarray analysis in our previous study. However, its function is incompletely understood. In this study, we confirmed that IFI6 was markedly induced in DENV infection of both primary HUVECs and EA.hy926 cell lines. Recombinant EA.hy926 cell lines in which IFI6 was either over-expressed (IFI6+/+) or knocked-down (IFI6-/-) were generated. The activation of caspase-3 and intrinsic apoptosis-related protein caspase-9 were down-regulated in IFI6+/+ but up-regulated in IFI6-/- cells at 24-48 hrs post-infection. After incubation with DENV for 48 hrs, the mitochondrial membrane potential (Δψ(m)) was more stable in IFI6+/+ cells but reduced in IFI6-/- cells, as assayed by fluorescence staining with JC-1. We observed that Bcl-2 expression was increased in IFI6+/+ and decreased in IFI6-/- cells. By contrast, Bax expression was decreased in IFI6+/+ and increased in IFI6-/- cells. It is presumed that the anti-apoptotic function of IFI6 is expressed by regulating the rheostatic balance between bcl-2/bax expression and inhibition of Δψ(m) depolarization during DENV infection of vascular endothelial cells(VECs). In addition, the pro-apoptotic protein X-linked Inhibitor of Apoptosis (XIAP)-Associated Factor 1(XAF1) expression had been reported to be up-regulated and led to the induction of apoptosis in DENV2-infected VECs,but the relationship between XAF1 and IFI6 dengue virus-induced apoptosis in VECs warrants further study.